Dosa dan Tanggung Jawab Moral dalam Narasi Kain dan Habel Berdasarkan Kejadian 4:1-16 - Gita Kenan; Yustin Lola Sampe; Rande Pindan (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
This research explores the narrative of Cain and Abel in Genesis 4:1-16 to dissect the concepts of sin and moral responsibility within a modern Christian context. Amidst the rising tide of individualism and "bystander culture," ethical responsibility toward others is often neglected behind religious formalities. Utilizing a qualitative method with a biblical exegesis approach, this study analyzes narrative structures, the personification of sin, and the dynamics of the dialogue between God and Cain. The findings indicate that sin in this text is understood as a relational failure and a failure of self-mastery, where humans possess the moral authority to conquer destructive impulses. Cain's rhetorical question, “Am I my brother’s keeper?”, is identified as a form of moral erosion leading to social and ecological alienation. However, God’s provision of a “mark” for Cain affirms that divine justice is always accompanied by the grace of providence. This research concludes that moral responsibility is a fundamental essence of humanity that demands the integration of ritual piety and social integrity. These findings are expected to serve as an ethical framework for academic and ecclesiastical communities, particularly in restoring the commitment to be “keepers” of one another amidst contemporary moral crises.